ARCS Learning Model in Offline and Online Learning: A Narrative Literature Review - Srimaryani, Srimaryani; Yuliyanto, Riyan; Ariyati, Izza Milenia (FKIP Universitas Lampung, 2023)
The Covid-19 pandemic requires the implementation of offline learning to change to online. This condition is a challenge for teachers and students in generating learning motivation when studying online. This narrative literature review aims to empirically compare the ARCS (Attention, Relevance, Confidence, and Satisfaction) learning model with offline learning before the pandemic and online learning during the covid-19 pandemic. This article reviews and compares empirical research on the ARCS model in offline and online learning. The review of this article focuses on: (1) The ARCS model in offline learning before the covid-19 pandemic; (2) The ARCS model in online learning during the covid-19 pandemic and (3) a comparison of ARCS models in offline and online learning. The authors' findings show that the ARCS model consistently improves student motivation, learning outcomes, and activity in both offline and online learning. While other variables that are improved have differences between the ARCS model in offline and online learning, namely offline learning increases participation, collaboration, and persistence. Online learning successfully increases confidence, attention, and academic achievement. The Media used in offline learning places students as the subjects of learning activities, while in online learning the media used places students as actors in learning activities.Keywords: ARCS Model, Offline Learning, Online Learning, Covid-19DOI: http://dx.doi.org/10.23960/E3J/v6i2.233-243